SCHEDULE BUFFERS: A COMPLEMENTARY STRATEGY TO REDUCE THE VARIABILITY IN THE PROCESSES OF CONSTRUCTION - Gonzalez, Vicente; Alarcón, Luis (Revista Ingeniería de Construcción, 2003)
Construction schedules are critical to the success of construction projects, as they define the sequence, rhythm and duration of productive processes. However, the traditional construction schedules have not adequately coped with the variable nature of these processes that are reflected in interferences, delays and higher costs to attain a project efficiently. Even though there exist techniques based on Lean Production, such as, for instance, Last Planner which reduces the variability to reasonable levels, many projects either do not apply these techniques or there exist variability that is not controlled as yet. This investigation aims at using Schedule Buffers as a complementary strategy to protect from the production processes variability in the construction projects and also describes the main aspects of a Methodology of Management of Schedule Buffers in Repetitive Projects. This article addreses a number of issues: the problem of variability in construction, the main control techniques and construction schedules, the major investigations on Buffers in construction, and the conceptual aspects of a Methodology of Management of Schedule Buffers in Repetitive Projects. Existing literature show that there do exist any analytic models that permit determining optimum sizes of Buffers, nor methodologies to manage them appropriately. There is no conceptual structure that integrates the diverse types of Buffers that can be used in construction, so as to compare and evaluate their use (either jointly or separately). The use of optimumsized Buffers will facilitate the development of a construction schedule with a greater predictive capacity, as well as, an appropriate management of them will improve the production flow in site in the projects. This work is the preliminary development of a doctoral investigation supported by the Centro de Excelencia en Gestión de Producción, GEPUC, of the Pontificia Universidad Católica de Chile.